Kerja Sama Antara Masyarakat Dengan Pesantren Anwaar-Ul-Uloom Bontocani Sulawesi Selatan - Agus Agus; Mustamin Giling (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aimed to describe the cooperation between the community and the Anwaar-Ul-UloomBontocani Islamic Boarding School of South Sulawesi. The sub-problems studied were focused on 1) the process of communication between the community and the Anwaar-Ul-UloomBontocani Islamic Boarding School of South Sulawesi. 2) The Form of cooperation between the Community and the Anwaar-Ul-UloomBontocani Islamic Boarding School of South Sulawesi. To discuss these problems, it was conducted a data collection in the field by using observation, interview and documentation techniques. The data sources were the community and the Boarding School. The data were collected and processed by using qualitative descriptive analysis through data reduction, data presentation, and data verification or concluding. This research used a sociological approach. The results showed that: 1) the communication process between the community and the Anwaar-Ul-Uloom Bontocani Islamic Boarding School in South Sulawesi was well established, particularly the communication process with the government and community and religious leaders. 2) The form of cooperation between the community and the Anwaar-Ul-Uloom Bontocani Islamic Boarding School in South Sulawesi could be seen from the participation of the Boarding School in various social and religious activities, for example, social service activities, anniversary commemoration (freedom) of the Republic of Indonesia, Safari Ramadhan, and several other socio-religious activities.